Data warehousing and knowledge discovery 13th International Conference, DaWaK 2011, Toulouse, France, August 29-September 2,2011. Proceedings - DaWaK (Conference) 2011 Toulouse, France); Cuzzocrea, Alfredo; Dayal, Umeshwar; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Data Warehousing and Knowledge Discovery, DaWak 2011 held in Toulouse, France in August/September 2011. The 37 revised full papers presented were carefully reviewed and selected from 119 submissions. The papers are organized in topical sections on physical and conceptual data warehouse models, data warehousing design methodologies and tools, data warehouse performance and optimization, pattern mining, matrix-based mining techniques and stream, sensor and time-series mining.
Electronic reproduction.
Keywords: Data warehousing -- Congresses; Database searching -- Congresses; Data mining -- Congresses; Electronic books